Tinjauan Hukum atas Pembayaran Upah di Bawah Upah Minimum dalam Hubungan Kerja Sesuai dengan Undang-Undang Ketenagakerjaan - Aurellia Dianti; Dadan Taufik Fathurohman (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2026)
This study aims to analyze the validity of wage agreements below the minimum wage from the perspective of contract law and employment law, as well as the legal protection for workers against such practices. The study uses a normative juridical method with a statutory and conceptual approach. The results indicate that wage agreements below the minimum wage are, in principle, null and void because they contradict statutory regulations, except for micro and small businesses that meet certain requirements. Legal protection for workers is provided through preventive and repressive mechanisms, including labor inspection, industrial relations dispute resolution and the imposition of sanctions on employers who violate wage provisions.